The Digital Advantage: Accelerating Impact of the Digital Economy - Shokhista Akhunova; Asadbek Sotvoldiev (European Science Publishing, 2024)
This article investigates the profound influence of the digital economy in today's rapidly evolving economic landscape. "The Digital Advantage: Accelerating Impact of the Digital Economy" explores the multifaceted transformations triggered by digital technologies. From the efficiency gains of automation and artificial intelligence to the global connectivity that fosters international collaboration, this piece illuminates the diverse ways in which the digital economy is reshaping industries and driving progress. Join us as we unravel the unparalleled advantages of the digital era, showcasing how it acts as a powerful catalyst for accelerated growth and prosperity in various sectors.
Keywords: Digital Marketing, Online Platforms, Contemporary Business, Marketing Strategies, Digital Revolution, Social Media, Data Analytics.